IPS Teacher's Pedagogical Competence in Shaping Profile of Pancasila Students in SMP Negeri 1 Ungaran - Sarbun Hadi Sugiarto; Sutama Sutama (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study was to (1) describe the ability of Social Science teachers in managing classes at SMPN 1 Ungaran. (2) describe the ability of Social Science teachers in assessing student learning outcomes at SMPN 1 Ungaran. This type of research is qualitative. This research was conducted at SMPN 1 Ungaran. The main subjects of this research are the principal, teachers, and students. Methods of data collection using interviews, observation, and documentation. Data analysis begins with (1) organizing the data, (2) conducting the data analysis process, (3) analyzing the data on the site, and (4) drawing conclusions. Test the validity of the data using credibility, transferability, confirmability and dependability. The results showed that (1) Social Science teachers at SMPN 1 Ungaran were able to manage the class. This is shown by making various class settings such as seating arrangements and also installing ornaments on the classroom walls. Teachers create a conducive learning atmosphere by giving students' attention fairly, providing reinforcement, providing rewards and punishments, and integrating the values of the nation's character. Optimizing study groups and deepening material is also carried out by teachers, who are able to bring students to become champions in Social Science Olympiad activities and social studies subject competitions. (2) Social Science teachers at SMPN 1 Ungaran are able to assess student learning outcomes. Before carrying out the assessment activities, what is prepared by the Social Science teacher is to prepare an assessment schedule and also prepare a grid of instruments that includes competency standards, basic competencies, achievement indicators, assessment techniques, and also forms of assessment. The teacher also prepares a follow-up program from the results of the assessment carried out in the form of remedial and enrichment programs.